Analisis Kinerja Keuangan Laporan Realisasi Anggaran Pendapatan dan Belanja Daerah Kota Bogor Tahun 2014-2019 - Silvianingsih, Rika; Rani, Utpala (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
The purpose of this study was to determine the financial performance of Bogor City from 2014 to 2019 based on the calculation of five ratios, namely: independence ratio, ratio, fiscal degree, regional financial dependence ratio, effectiveness ratio of local revenue, and regional financial efficiency ratio. This type of research is carried out by quantitative research and the data used are secondary data taken from ppid.kotabogor.go.id. The results of this study indicate that the financial performance of the city of Bogor is fine when measured by the Regional Financial Independence Ratio, Effectiveness Ratio of Regional Original Income, and the Degree Ratio of Fiscal Decentralization, but the Regional Financial Dependency Ratio does not optimize income from other sectors, resulting the level of dependence on funds transfers are still very high and the Efficiency Ratio is less efficient because the regional expenditure is greater than the regional income received.